2015
DOI: 10.4238/2015.november.13.3
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the gene-protein interaction network in glioma

Abstract: ABSTRACT. Glioma is the most aggressive type of brain tumor. Great progress has been achieved in glioma treatment, but the protein-protein interaction networks underlining glioma are poorly understood. We identified the protein-protein interaction network for glioma based on gene expression and predicted biological pathways underlying the molecular complexes in the network. Genes involved in glioma were selected from the Online Mendelian Inheritance in Man (OMIM) database. A literature search was performed usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Cytokine networks play important regulatory roles in inflammatory immune responses to cancer including glioma 3941. Cytokines are also involved in chronic inflammation that may lead to carcinogenesis 39.…”
Section: Discussionmentioning
confidence: 99%
“…Cytokine networks play important regulatory roles in inflammatory immune responses to cancer including glioma 3941. Cytokines are also involved in chronic inflammation that may lead to carcinogenesis 39.…”
Section: Discussionmentioning
confidence: 99%
“…Human MEG3 is an imprinted DLK1-MEG3 locus gene and is located in chromosome 14q32. 37,38 MEG3 has previously been shown to mediate tumorigenesis through its interaction with miRNAs. MEG3 has been found in various normal tissues, but MEG3 expression is often absent in tumor tissues because of its gene deletion and promoter hypermethylation.…”
Section: Discussionmentioning
confidence: 99%
“…Human MEG3 is an imprinted DLK1‐MEG3 locus gene and is located in chromosome 14q32 . MEG3 has previously been shown to mediate tumorigenesis through its interaction with miRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al integrated gene interaction information into a weighted random survival forest method to perform an accurate survival prediction and to discover a survival biomarker for glioma [ 5 ]. Zhou et al identified the glioma-specific protein interaction network based on bulk RNA-seq data and performed enrichment analysis to verify disease-specific molecular complexes [ 6 ]. Due to the complexity of glioma, more genetic markers need to be discovered.…”
Section: Introductionmentioning
confidence: 99%